Increasing access to evidence-based treatment for child anxiety problems: online parent-led CBT for children identified via schools - Green, I; Reardon, T; Button, R; Williamson, V; Halliday, G; Hill, C; Larkin, M; Sniehotta, FF; Ukoumunne, OC; Ford, T; Spence, SH; Stallard, P; et al. (Wiley, 2022)
Background Anxiety problems are extremely common and have an early age of onset. We previously found, in a study in England, that fewer than 3% of children with an anxiety disorder identified in the community had accessed an evidence-based treatment (Cognitive Behavioural Therapy; CBT). Key ways to increase access to CBT for primary school-aged children with anxiety problems include (a) proactive identification through screening in schools, (b) supporting parents and (c) the provision of brief, accessible interventions (and capitalising on technology to do this).